MENENTUKAN VARIABEL YANG PALING BERPENGARUH TERHADAP KINERJA POMPA HIDRAM MENGGUNAKAN METODE ESTIMASI EFEK ALGORITMA YATES - Ibrahim, Maulana Malik; Dezya Aditya Pratama; Nata, Yudi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
In each study, often many variables are used and interrelated with each other. The increasing number of variables often confuses which variables are the most dominant for changes or desired results.Many methods are used to find the most dominant variable in influencing the research output.Factorial 2 3design with estimated effects of Yates algorithm is a method that can be used to find the most dominant variable in influencing output. This study aims to find the most dominant variable on the output pressure generated by the hydram pump. The results calculated using this method are the result of flow simulations in pumps with CFD [1]. Variables used are valve opening, a height of the water flow, and valve type. The greater the velocity of water flow in the drive pipe, the greater the flow rate of the water in the delivery pipe and the flow rate of the pressure valve. The drag coefficient of the ball valve press model is smaller than the valve press plate model, so it requires a smaller force to open and close the valve. In accordance with the valve on the hydram pump which requires the process of opening and closing the valve must be fast so that it can provide better performance [2]. The simulation results also show that the most optimal step valve press length is at the valve opening-diameter ratio of 0.16. This research is expected to provide input on the design of the hydram pump in the future